2003
DOI: 10.1034/j.1600-0447.2003.02377.x
|View full text |Cite
|
Sign up to set email alerts
|

Affective disorder and ‘psychopathy’ in a sample of younger male delinquents

Abstract: The inverse relationship between threatening events and the PTSD diagnosis seems to indicate other coping modalities than those found in 'non-psychopaths'. That finding is discussed against the background of psychophysiological data and psychosocial learning models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Blackburn’s (1975) “secondary psychopath,” similar to Hicks, Markon, Patrick, Krueger, and Newman’s (2004) “aggressive psychopath,” is described as anxious, depressed, hostile, and impulsive. This subtype appears to reflect the emotional dysregulation and interpersonal ambivalence features of BPD and is consistent both with psychopathy’s covariation with the diagnoses of both ASPD and BPD (Moeller & Hell, 2003) and with the finding that individuals who are high in the components of PCL-R Factor 2 are more likely to meet the criteria for BPD (Blackburn & Coid, 1998). The association of aggressive psychopathy with BPD is consistent with the finding that emotional dysregulation may mediate the relation between BPD and violence (Mancke, Herpertz, Kleindienst, & Bertsch, 2017; Newhill, Eack, & Mulvey, 2012).…”
Section: Bpdsupporting
confidence: 69%
“…Blackburn’s (1975) “secondary psychopath,” similar to Hicks, Markon, Patrick, Krueger, and Newman’s (2004) “aggressive psychopath,” is described as anxious, depressed, hostile, and impulsive. This subtype appears to reflect the emotional dysregulation and interpersonal ambivalence features of BPD and is consistent both with psychopathy’s covariation with the diagnoses of both ASPD and BPD (Moeller & Hell, 2003) and with the finding that individuals who are high in the components of PCL-R Factor 2 are more likely to meet the criteria for BPD (Blackburn & Coid, 1998). The association of aggressive psychopathy with BPD is consistent with the finding that emotional dysregulation may mediate the relation between BPD and violence (Mancke, Herpertz, Kleindienst, & Bertsch, 2017; Newhill, Eack, & Mulvey, 2012).…”
Section: Bpdsupporting
confidence: 69%
“…PTSD was reported to be the most common anxiety disorder diagnosis in this sample; however, its prevalence was not reported in either the total sample or the psychopathic subsample. Conversely, Moeller and Hell (2003) reported that none of the high psychopathic offenders from their sample of male prisoners met diagnostic criteria for PTSD, despite a significant correlation between PCL-R total scores and number of traumatic experiences.…”
Section: Psychopathy: Theoretical and Empirical Links With Trauma Expmentioning
confidence: 93%
“…They suggested that in some individuals the association between early childhood victimization and violence might be mediated by psychopathy. In a Swiss sample of younger male offenders (age 17–27), PCL-R total scores were significantly correlated with the number of prior threatening events experienced [22]. Recently, Verona, Hicks, and Patrick [23] reported that, among female offenders, experiences of both physical and sexual abuse correlated with PCL-R total scores and with scores on the affective-interpersonal and antisocial lifestyle dimensions of psychopathy.…”
Section: Introductionmentioning
confidence: 99%